A high strength asymmetric polymer–inorganic composite solid electrolyte for solid-state Li-ion batteries. (1st February 2022) - Li, Yuan; Yang, Liwen; Dong, Ran; Zhang, Tongwei; Yuan, Jialiang; Liu, Yang; Liu, Yuxia; Sun, Yan; Zhong, Benhe; Chen, Yanxiao; Wu, Zhenguo; Guo, Xiaodong
Abstract: All solid-state lithium metal batteries (ASSLMBs) are regarded as one favorable future technology for energy storage. Composite solid-state electrolytes (CSEs) exploit the strengths of both solid polymer electrolytes (SPEs) and inorganic ceramic electrolytes (ICEs), which commonly exhibit enhanced ionic conductivity, as well as excellent cycling stability, and favorable interfacial resistance. However, rational structure design for better CSE/electrodes interface contact is necessary for the future practical applications. Herein, an asymmetrical composite solid electrolyte is constructed by introducing the electro-spun polyacrylonitrile (PAN) into the casting membrane. Oxidation-resistant PAN shows strong adsorption of Li-salt anions, providing long range Li + transmission path and extended electrochemical window and protections for bottom oxidative polyethylene oxide (PEO) -based layer. Meanwhile, the bottom PEO/garnet Li6.4 La3 Zr1.4 Ta0.6 O12 (LLZTO) matrix obtains good ion conductivity and stability to Li metal anode, and successfully protects the antioxidative PAN for possible severe side reactions with anodes. Obtained bilayer CSE shows high ionic conductivity ( 6.0 × 10 − 4 S cm −1 at 60 °C), broad electrochemical window (5.2 V, vs . Li/Li + ), and good mechanical properties. The battery displays 159.9 mA h g −1 and remained 153.5 mA h g −1 after 90 cycles at 0.2 C rate and good inhibition to lithium dendrites growth and side reactions. This work indicates that the asymmetric designed CSE film provides a possible directions towards future high energy density ASSLMBs. Graphical abstract: The asymmetrically designed solid-state electrolyte with electro spun oxidation-resistant poly(acrylonitrile) presents high strength, enhanced ionic conductivity, and excellent cycling performance, which is a promising choice for future ASSMBs. Image, graphical abstract